(untitled) (Marketing Journal, 2025)
This article analyzes the role of corporate governance systems in enhancing the competitiveness of industrial enterprises and examines the key factors contributing to its effectiveness. Specifically, it explores components such as transparency in decision - making processes, strategic balance between management and ownership, the robustness of internal control mechanisms, and systematic engagement with 452 stakeholders. The study also evaluates the current implementation status of these governance principles in industrial enterprises of Uzbekistan and proposes improvement strategies based on advanced international practices. The research findings offer scien tific and practical recommendations for strengthening enterprisesʼ competitive advantages from a strategic management perspective.